Pelaksanaan Ekstrakurikuler Seni Tari di SMK Nusatama Padang - Rahadatul Aisy Yumar; Tulus Handra Kadir (Journal of Creative Student Research, 2024)
This study aims to find out and describe how the implementation of dance extracurricular arts at SMK Nusatama Padang. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the extracurricular activities of dance arts at SMK Nusatama Padang consist of planning and implementation. The planning of the dance extracurricular activity program at SMK Nusatama Padang has been well coordinated and appropriate according to the plan made by the coach starting from the schedule, time, in accordance with the purpose of the program. The implementation of dance extracurricular activities at SMPN 2 Kandis has gone well and the coach tries his best to make the students who participate in the activity practice well according to the schedule and place. Appreciation of coaches and coaches by displaying students' dance works is one of the motivations for students to continue practicing so that they are more confident in displaying the results of exercises that have been done well.